Kajian Konsep Kecerdasan Spiritual berdasar Kisah Luqman dalam Al-Qur’an - Noer Rohmah; Roihanah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2022)
Spiritual intelligence is an important study in the world of education because of its impact and role in shaping meaningful human beings in life. Humans who have closeness to God as well as concern for others. For this reason, Islamic education requires a concept of spiritual intelligence that can be applied to form a generation of Muslims with this type of intelligence. This study seeks to produce the concept of spiritual intelligence based on the verses of the Qur'an, about the Luqman family story contained in Surah Luqman verses 12-19. Through library research, data was collected using documentation techniques, then analyzed using the maudhu'i or thematic method, by discussing the verses of the Qur'an based on the theme. The results of the study explain that there are several aspects of spiritual intelligence in the surah and the verse, namely: spiritual aspects which include the command to be grateful, not to commit shirk, being able to do good and prevent evil, and being able to be patient. Furthermore, the biological aspect is the command to establish prayer and the social aspect which includes: the necessity to always obey both parents and get along with fellow humans with good association. Then some aspects of this spiritual intelligence can be actualized in the implementation of the pillars of Islam, the pillars of faith and ihsan.